Educação superior indígena na UnB: perfil, trajetória, expectativas e desafios dos estudantes - Renault, Cláudia Regina Nunes dos Santos (2019)
The University of Brasília (UnB) was pioneer in offering specific vacancies to indigenous people, and in 2004 signed a Cooperation Agreement with the National Indian Foundation (FUNAI). This agreement established the creation of additional vacancies and specific entrance exams for indigenous students. In 2012, with the promulgation of the "quota law" (Law nº 12.711), it became mandatory to reserve vacancies at federal universities for blacks and indigenous people. After 14 years of the Cooperation Agreement and six of the quota law, information regarding the status of these students in UnB is still negligible. The present work aims to characterize the indigenous students of UnB, to analyze their academic trajectory, expectations and difficulties. For that, an exploratory, descriptive, mixed research was carried out in two stages. In the first stage, with a documentary and quantitative nature, information was collected from all indigenous population of the UnB, which was included in the 2004 Cooperation Agreement, regarding the following variables: age, sex, ethnicity, course, date of entry, and academic situation (studying, on leave, drop out, complete) . This information was extracted from the University's Undergraduate System (SIGRA). In the second phase, with a qualitative nature, nine indigenous students, between studying, on leave or drop out, were interviewed with the objective of understanding their expectations and difficulties related to graduate. A total of 108 indigenous students, with a average age of 24.39 years, from all regions of the country and belonging to 35 different ethnic groups were identified. Of the total number of students, 26.9% completed the graduation on time and 43.5% were disconnected from the university. Content analysis and categorization of interview data were done. Among the expectations presented by the students, the perspective of return and contribution to the community itself or even other indigenous communities stands out. The reported difficulties were diverse and can be grouped into three main categories: personal, institutional and cultural. Among the personal difficulties is the distance from the family. As institutional difficulties, the irregularity in the transfer of scholarships and the lack of support / guidance are reported repeatedly. Finally, among the cultural difficulties, the language and the low ethnic-cultural diversity in the university were pointed. In summary, the data shows the cultural diversity of the group of indigenous students and indicate higher levels of drop outs among them than those of higher education in general. These data, added to the difficulties reported by the students, suggest that this affirmative action has been effective in guaranteeing the entry of indigenous people into the University, however, mechanisms favoring their stay in the university and completion of higher education by the indigenous population need to be improved.